Students’ Demand for Guidance from Academic Administration, College of Politics and Governance, Mahasarakham University - เรืองสุวรรณ วิไลวรรณ (Journal of Politics and Governance, 2018)
The objectives of this research were to examine the level of demand for guidance on academic, career, personal, and social respect, and compared the demand for guidance on academic, career, personal, and social respect by gender, academic achievement, and college years of 204 students in College of Politics and Governance, Mahasarakham University, Academic Year 2015. The sample group was selected with stratified sampling method. Questionnaire with 45 questions about the demand for academic guidance was used as the research tool. Statistics used were mean, standard deviation, t-test (Independent Sample) and F-test (One-way Analysis of variance), and Sheffe’s method of paired comparison. Findings illustrated that the demand of students in College of Politics and Governance, Mahasarakham University, for guidance on academic, career, personal, and social respect was in high level. Considering by respect, it was found that the demand for guidance on career was in the highest level, followed by academic, personal, and social respect respectively. Furthermore, male and female students had similar demand for guidance, in overall and by respect. It was found that the students with the high, average, and low academic performance had no difference on demand for guidance, both in overall and by respect. Students in the first-year to the fourth-year had different level of demand for guidance on academic, career, personal, and social respect with statistical significance .05. The third-year students had less demand for guidance in overall than the first-year and second-year students. Moreover, the third-year students had less demand for guidance on career, personal, and social respect than the first-year and the second-year students with statistical significance .05